A SEMANTIC ANALYSIS OF COMMON ERRORS: EVALUATING THE LIMITS OF ONLINE TRANSLATION APPLICATIONS - Siumarlata, Viktor; Sallata, Yizrel Nani; Tandikombong, Matius; Rachel (FKIP Unismuh Makassar, 2024)
This article examines the evaluation of translation errors made by using online translation applications. Online translation applications are increasingly important for cross-language communication, but their quality often contains errors and defects. The research uses qualitative methods with a descriptive analysis approach, focusing on sixth-semester English students at the Indonesian Christian University of Toraja. The study consists of 10 Indonesian sentences translated into English using an online translation application. The results of semantic analysis show significant translation errors, including context-related errors, loss of nuance, and word choice errors. Inconsistencies in translation between sentences are also observed. The article emphasizes the importance of human skills in translation and double-checking translation results. It emphasizes the need for a deeper understanding of context and nuance. While online translation apps can be useful tools, careful and critical evaluation is still essential to ensure optimal quality in cross-language communication.